Improving reliability in MAS by rule-based logic and cryptographic techniques. (13th April 2020) - Mishra, Prashant Kumar; Singh, Raghuraj; Yadav, Vibhash
Mobile agent (MA) is a composition of software paradigm, having the capability to move from one host to another across dynamic network environment and execute task assigned by its user. Reliability is one of the most important issues in mobile agent-based system (MAS) which was addressed by many researchers. In this paper, we enhance the reliability in MAS with the support of intrusion detection system (IDS) and effective routing. Routing is an important process to find optimal path which improves network throughput and reliability. Collision-free ( CF ) – network graph exploration method is designed for identifying optimal path for MAs. Security is a crucial aspect due to various malicious node activities and must be considered while estimating reliability. In our process, HMAC-SHA1 algorithm is performed for detecting malicious agent and rule-based logic (RBL) is designed to identify malicious host. Further, we calculate reliability of MAS with respect to status of network and its condition which includes link connectivity and malicious node probability. Finally, we are simulating our performance by using various factors such as size of MAS, malicious ratio and number of mobile agents in MAS, etc. These factors are significant to show improved reliability of our proposed system.